Preventive justice - Ashworth, Andrew; Zedner, Lucia (Oxford : Oxford University Press, 2014)
'Preventative Justice' looks at the use of coercive preventive measures by the state, both within and beyond criminal law. Examining preventive laws, measures, and institutions in and outside the criminal law, it explores the justifications given for using coercion to protect the public from harm.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on April 23, 2014).
Keywords: Preventive law; Criminal law -- Philosophy